Incidence and Etiology of Late Preterm Admissions to the Neonatal Intensive Care Unit and Its Associated Respiratory Morbidities When Compared to Term Infants - Mally, Pradeep V.; Hendricks-Muñoz, Karen D.; Bailey, Sean (American Journal of Perinatology, 2013)
Objective To determine etiology of neonatal intensive care unit (NICU) admission and acute morbidities in late preterm (LPT) neonates.Methods Neonates admitted at New York University Langone Medical Center's NICU were grouped as follows: period 1: all LPT neonates with gestational age between 340/7 and 366/7 weeks and born between January 2006 and June 2007; period 2: all term neonates born between January 2007 and June 2008. Neonatal and maternal data were collected from both the groups and compared.Results Thirty-three percent of LPT births were admitted to the NICU, compared with 7% of term births (p < 0.05). LPT neonates had an increased incidence of low birth weight, hypoglycemia, hypothermia, and hyperbilirubinemia as an admission diagnosis (p < 0.001). The overall incidence of respiratory distress syndrome (RDS) was 9%, 4%, 3%, 0.7%, 0.2% and 0% in 34-week, 35-week, 36-week, 37-week, 38- to 39-week, and 40-week gestational age neonates (p < 0. 001).There was an increased incidence of RDS and persistent pulmonary hypertension, along with an increased need for surfactant replacement therapy, continuous positive airway pressure, and ventilator support in the LPT group when compared with the term neonates (p < 0.001).Conclusions LPT neonates are at increased risk for hypothermia, hypoglycemia, hyperbilirubinemia, and respiratory morbidity requiring increased respiratory support when compared with term neonates.
Keywords: late premature neonate; term neonate; morbidities; neonatal intensive care unit